2021
DOI: 10.3389/fpls.2021.620018
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Mineral Nutrition Transport and Signal Transduction in Rosaceae Fruit Quality and Postharvest Storage

Abstract: Mineral nutrition, taken up from the soil or foliar sprayed, plays fundamental roles in plant growth and development. Among of at least 14 mineral elements, the macronutrients nitrogen (N), potassium (K), phosphorus (P), and calcium (Ca) and the micronutrient iron (Fe) are essential to Rosaceae fruit yield and quality. Deficiencies in minerals strongly affect metabolism with subsequent impacts on the growth and development of fruit trees. This ultimately affects the yield, nutritional value, and quality of fru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 135 publications
2
26
1
Order By: Relevance
“…K and Cu were also found as differentiation markers for the geographical origin of honey [ 22 ] and might be related to agricultural practice. In their review paper, Bai, Shen, and Huang [ 24 ] explained that the use of potassium (K) fertilizer for fruits (pear, apple, cherry, etc.) leads to better development of the plants, increases nutritional concentrations of fruit, and prevents the appearance of certain destructive diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…K and Cu were also found as differentiation markers for the geographical origin of honey [ 22 ] and might be related to agricultural practice. In their review paper, Bai, Shen, and Huang [ 24 ] explained that the use of potassium (K) fertilizer for fruits (pear, apple, cherry, etc.) leads to better development of the plants, increases nutritional concentrations of fruit, and prevents the appearance of certain destructive diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Boron and Cu, together with Fe, Mn, Zn, Mo, Ni, and Cl, are part of the micronutrient group required for the plant’s growth [ 25 ]. Boron is directly involved in plant metabolism and has an important function in pollen germination and pollen tube growth [ 24 ]. The effect of boron fertilization on fruit trees, on fruit quality, has been well known for many years [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…erefore, an increase in photosynthesis activity allows the solutes to move inside the plants and facilitate the expression of plants to accumulate sugars inside the fruit [30]. Low levels of phosphorus in soil result in low concentrations of galactaric acid, lysine, vitamin C, proline, and citrate and thus results in a significant change in bioactive compounds in different fruits [31]. Our results showed that soils and fruits of higher elevations are rich in micro-and macronutrients (Table 3).…”
Section: Discussionmentioning
confidence: 67%
“…These mineral elements play a key role in the physiological processes of plants. Mineral nutrition indeed strongly affects plant metabolism and ultimately affects plant growth, fruit development, fruit quality, nutrition, and postharvest storage [82]. Besides, mineral nutrition, such as N, P, and Fe, not only directly affects fruit quality but also influences the absorption and the content of other nutrient elements.…”
Section: Discussionmentioning
confidence: 99%